Experimental investigation on the flow condensation of R450A, R515B, and R1234ze(E) in a 7.0 mm OD micro-fin tube. (1st November 2022) - Diani, Andrea; Liu, Yuce; Wen, Jian; Rossetto, Luisa
Highlights: R450A, R515B, and R1234ze(E) tested during condensation in a 6.14 mm ID micro-fin tube. R515B and R1234ze(E) showed similar heat transfer coefficients, R450A higher values. R450A showed frictional pressure gradients lower than R515B and R1234ze(E). Experimental HTC and pressure gradient compared against values calculated with models. Abstract: The flow condensation of R1234ze(E), R450A, and R515B was conducted in a 6.14 mm inner diameter micro-fin tube. The fin height is 0.18 mm and the fin number is 50. The helix angle is 18° and the area enhancement factor is 1.63. During the experimental tests, the saturation temperature is 30 and 40 °C. The mass fluxes range from 50 to 400 kg m -2  s -1 . The vapor qualities are between 0.1 and 0.96. The heat transfer coefficients and frictional pressure gradients of the three refrigerants were compared with each other. The experimental heat transfer coefficient increases with vapor quality and mass velocity, except at high vapor quality, where a higher mass velocity does not imply a higher heat transfer coefficient, probably due to the liquid film thickness distribution. Generally speaking, R450A presents slightly higher heat transfer coefficients at high mass fluxes and smaller pressure gradients, whereas R515B shows lower heat transfer coefficients and pressure drops very close to those of R1234ze(E). Moreover, some models of the heat transfer coefficient and pressure gradient specifically developed for micro-fin tubes were chosen to explore their feasibility for the new refrigerants and tube. Cavallini et al.'s model shows the best agreement for the heat transfer coefficient, and Diani et al.'s model shows the best agreement for the frictional pressure gradient.